Exploring the reasons for defaulting from childhood immunization: a qualitative study in Pakistan - Kifayat Ullah; Javeria Saleem; Rubeena Zakar; Muhammad Ishaq; Farhad Ali Khattak; Fatima Majeed; Hafiza Aisha Sadiqa; Florian Fischer (BMC, 2024)
Abstract Background Childhood vaccination is widely recognized as the most effective means to prevent various diseases. However, a considerable amount of children still miss out on their vaccination schedules. Therefore, this study explores the reasons for defaulting from the expanded program on immunization in district Swat, Pakistan. Methods A qualitative phenomenological approach was used. Data collection took place from March to September 2022. Thirty-six in-depth interviews were conducted with participants who had defaulter children. The collected qualitative data were analysed thematically to identify key patterns and themes related to the reasons for defaulting from childhood vaccination schedules. Results Six themes emerged, i.e., illness of the defaulter child at the scheduled time, perceived side effects of the vaccination, factors related to caregivers, myths and misconceptions, vaccinators attitudes and crowed vaccination centres, as well as poor immunization service arrangements. Four subthemes arose related to caregivers, such as lack of clear understanding about completion of vaccination, least priority for child's vaccination, cultural restriction on mothers, and the loss of vaccination card. Conclusion According to the study's findings, caregivers have their own perceptions regarding the non-completion of their children's vaccination schedule. The childhood immunization defaulting arises from various factors including child illness, Adverse Events Following Immunization (AEFIs) concerns, misconceptions, improper injection techniques, and negative vaccinator attitudes. The vaccination completion rate may be increased if the concerns of the caregivers are appropriately addressed.